PENGEMBANGAN POTENSI KELOKALAN DESA KARANGPATIHAN DALAM PENGEMBANGAN WISATA BERBASIS MASYARAKAT - Wardhani, Windi Novia Ratri; Pratiwi, Ratih - (Fokus ABDIMAS, 2024)
Engagement with the community is not only an implementation of the third pillar of the Tridharma of Higher Education but also a strategic step to enhance the execution of the pillars of education, research, and community service. The village of Karangpatihan, previously known as the 'village of the intellectually disabled' due to a high number of residents with intellectual disabilities, has undergone positive changes through collaborative efforts with Rumah Harapan. Through this initiative, our goal is to develop the local potential of the village by supporting training programs in skills development, local product marketing, and community-based tourism promotion. In this context, we conducted a mini-workshop titled "Development of the Local Potential of Karangpatihan Village in Community-Based Tourism Development" for 30 young individuals affiliated with Karang Taruna. The method employed in this community engagement is training and mentoring for the younger generation in identifying elements of local potential and the developmental process towards becoming a pilot tourist village. The outcomes of this engagement demonstrate strategic steps to develop local potential and advance the tourism sector sustainably and inclusively. These steps include, identifying local potential; involving active community participation to tourism development; organizing tourism skill training programs; and building partnerships and collaborations to support infrastructure and sustainable tourism promotion. Keywords: intellectual disabilities; tourist village; local potential of Karangpatihan Village.